FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL - Mey Chyndiz; Sari Rusmita (Fakultas Ekonomi dan Bisnis Islam, 2021)
Introduction: This study aimed to determine the effect of profitability, Company Size and Structure of Capital Structure Assets against the state-owned company listed on the Indonesia Stock Exchange in 2012 - 2016 partially. Background Problem: The era of globalization has resulted in increasingly sharp competition, so that every company is required to always produce efficiently if they want to remain competitive. One of them is by paying attention to spending which ultimately has an impact on the balance of the company which can be seen from the capital structure owned by the company. Research Methods: The population in this study is a state-owned company that published annually by the Indonesia Stock Exchange in 2012 - 2016. The sampling technique used purposive sampling and obtained a sample of 15 SOEs. Testing the hypothesis in this study using multiple linear regression analysis. Results: These results indicate that profitability had a significant impact on the capital structure with a constant value is negative. The size of the company has a significant impact on the capital structure with a constant value is negative. While the structure of assets has a significant impact on the capital structure by value is negative. Profitability, company size, and structure of assets has the effect of 64.6% of the capital structure and the remaining 35.4% is influenced by other variables not included in this study. Conclusion: Capital Structure is influenced by Profitability, Company Size and Asset Structure